NATURAL RESOURCES OF SAGURAMO PRESERVE (Conferencea, 2024)
In 2017-2021, on the basis of the monitoring carried out in different areas of the Saguramo Reserve, we created the first synopsis of the natural resources of the Saguramo Reserve, including about 400 species, distinguished with biodiversity of the flora of Georgia. The current state of their populations was analyzed; A computer database of both widely represented and rare and endangered species (affected by anthropogenic or natural hazards) was created, taking into account the modern requirements of taxonomy and nomenclature.